2019
DOI: 10.1111/nyas.14091
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial‐resistant bacterial infections from foods of animal origin: understanding and effectively communicating to consumers

Abstract: Consumers are increasingly interested in the attributes of the food they consume. This includes what is in the food and how it was raised; and at least some consumers are willing to pay a premium for products with specific attributes. However, the current plethora of labels on the market does not adequately address this issue; rather than providing actionable information, most labels add to the consumer confusion. In addition, there is a tendency toward “absence labels” that can contribute to a negative consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…In 2009, the Food and Drug Administration concluded that the use of antibiotics for growth promotion should be eliminated. Long term subtherapeutic antibiotic usage in food-producing animals was identified to contribute to the development and spread of bacterial resistance [ 16 , 17 , 18 , 19 ], which could be transmitted between humans and animals [ 20 , 21 ] via direct contact or through environment [ 22 , 23 ]. In 2014, the World Health Organization concluded that the use of antibiotics as feed additives for food animals was a public health issue as many antimicrobial agents in farm animal production were also important in treating human infections [ 24 ].…”
Section: “No Antibiotics Ever” Broiler Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2009, the Food and Drug Administration concluded that the use of antibiotics for growth promotion should be eliminated. Long term subtherapeutic antibiotic usage in food-producing animals was identified to contribute to the development and spread of bacterial resistance [ 16 , 17 , 18 , 19 ], which could be transmitted between humans and animals [ 20 , 21 ] via direct contact or through environment [ 22 , 23 ]. In 2014, the World Health Organization concluded that the use of antibiotics as feed additives for food animals was a public health issue as many antimicrobial agents in farm animal production were also important in treating human infections [ 24 ].…”
Section: “No Antibiotics Ever” Broiler Productionmentioning
confidence: 99%
“…The removal of subtherapeutic AGPs has resulted in poor flock performance, reduced daily gain, increased risk of enteric issues, low water consumption, and high mortality [ 22 , 30 ]. Average monthly mortality in NAE broilers is 25–50% higher than conventional broiler chickens [ 31 ]; mortality in NAE broilers averages about 4.2% compared to conventional broiler mortality at 2.9% [ 22 ]. Higher mortality in NAE couples with an increased incidence of multiple bacterial diseases, including NE and colibacillosis.…”
Section: “No Antibiotics Ever” Broiler Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Ritter et al . explores risk communication in this realm . Further, the authors describe research on what currently drives consumers to choose “raised without antibiotics” meat and poultry products over conventionally raised products and the impacts of this niche market sector on animal health and welfare; they also explore plausible alternatives to such “never, ever” policies, relying instead on process‐verified programs that blend animal welfare, environmental, and antimicrobial stewardship principles.…”
Section: Communicating Risks Concerning Amr In the Food Chainmentioning
confidence: 99%
“…The paper by Ritter et al explores risk communication in this realm. 13 Further, the authors describe research on what currently drives consumers to choose "raised without antibiotics" meat and poultry products over conventionally raised products and the impacts of this niche market sector on animal health and welfare; they also explore plausible alternatives to such "never, ever" policies, relying instead on process-verified programs that blend animal welfare, environmental, and antimicrobial stewardship principles. Raising food animals in an ethical manner that ensures the health and welfare of the animal, employing sustainable environmental practices, and providing transparency regarding antimicrobial uses at an enterprise level offers the greatest opportunity for useful, open, and honest communications with consumers.…”
Section: If You Think You Understand Antimicrobial Resistance It Hasmentioning
confidence: 99%